Wainwright's Favourite Lakeland Mountains - Wainwright, A. (London Michael Joseph, 1999)
The author describes the splendour of twenty of Lakeland's principal fells, which have the status of mountains. He describes the various routes to each summit, the special or nearby features and the glory of each conquest. He describes such places as Helvellyn, Skiddaw and Fairfield
Include Color Illustration and Index
Keywords: England--Lake District -- England--Lake District National Park